2020
DOI: 10.1002/dad2.12033
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiles of incident mild cognitive impairment and Alzheimer's disease among adults with Down syndrome

Abstract: Introduction We sought to determine if proteomic profiles could predict risk for incident mild cognitive impairment (MCI) and Alzheimer's disease (AD) among adults with Down syndrome (DS). Methods In a cohort of 398 adults with DS, a total of n = 186 participants were determined to be non‐demented and without MCI or AD at baseline and throughout follow‐up; n = 103 had incident MCI and n = 81 had incident AD. Proteomics were conducted on banked plasma samples from a previously generated algorithm. Results The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…agnostic process can meet these needs, 1 and have shown that bloodbased biomarker profiles can be an accurate first step in detecting AD, 2,3 mild cognitive impairment (MCI), 4 Parkinson's disease, 5 dementia with Lewy Bodies, 6 as well as AD and MCI among adults with Down syndrome. [7][8][9] With the shift in diagnostic framework for AD to AT(N), increased work has been conducted looking at the utility of neurodegenerative biomarkers (N) in addition to amyloid beta (A) and tau (T). 10 One of…”
Section: Introductionmentioning
confidence: 99%
“…agnostic process can meet these needs, 1 and have shown that bloodbased biomarker profiles can be an accurate first step in detecting AD, 2,3 mild cognitive impairment (MCI), 4 Parkinson's disease, 5 dementia with Lewy Bodies, 6 as well as AD and MCI among adults with Down syndrome. [7][8][9] With the shift in diagnostic framework for AD to AT(N), increased work has been conducted looking at the utility of neurodegenerative biomarkers (N) in addition to amyloid beta (A) and tau (T). 10 One of…”
Section: Introductionmentioning
confidence: 99%
“…Niklas et al binarized the AT(N) markers (A: CSF Aβ42 and amyloid-PET; T: CSF phosphorylated tau and tau PET; and N: hippocampal volume, temporal cortical thickness, and CSF neurofilament light (NfL)) and found that using different AT(N) variants might cause important prognostic information to be lost because they were not interchangeable, and that optimal variants differ by clinical stage [ 5 ]. Blood-based biomarkers represent a significant alternative to a primary care-based screening algorithm for AD, given the high prevalence of the disease [ 3 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most AD biomarker identification is conducted using only one type of blood fraction [ 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Although both serum and plasma have been used in developing blood-based biomarker profiles, serum has been used more frequently and has demonstrated higher sensitivity in AD detection [ 6 , 7 , 8 , 9 , 10 , 11 ] than plasma. Combined assays from each of the blood fractions has not been used in blood-based biomarker profiling.…”
Section: Introductionmentioning
confidence: 99%
“…This number is projected to nearly triple by 2060 ( Prevention, 2021 ). Machine Learning (ML) methods for AD and AD Related Dementias (ADRDs) is growing faster than ever before ( Waring et al, 2008 ; Magnin et al, 2009 ; O'Bryant et al, 2011a ; O'Bryant et al, 2011b ; O'Bryant et al, 2013 ; O'Bryant et al, 2014 ; Weiner et al, 2015 ; O'Bryant et al, 2016 ; O'Bryant et al, 2017 ; Grassi et al, 2018 ; Hampel et al, 2018 ; O'Bryant et al, 2018 ; Stamate et al, 2019 ; Zetterberg and Burnham, 2019 ; Zhang and Sejdić, 2019 ; Franzmeier et al, 2020 ; O'Bryant et al, 2020 ; Rodriguez et al, 2021 ). A PubMed search using keywords of AD and ML showed that the number of publications related to ML for AD has increased by 146 percent from just two in 2006 to 294 in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…A PubMed search using keywords of AD and ML showed that the number of publications related to ML for AD has increased by 146 percent from just two in 2006 to 294 in 2020. For example, O'Bryant et al developed a Support Vector Machine (SVM) model with 398 plasma samples obtained from adults with Down syndrome to predict incident mild cognitive impairment (MCI) (AUC = 0.92) and incident AD (AUC = 0.88) ( O'Bryant et al, 2020 ). O’Bryant et al also developed a precision medicine model for targeted NSAID therapy in AD based on data collected from a previously conducted clinical trial.…”
Section: Introductionmentioning
confidence: 99%